Globalizing automobilism : exuberance and the emergence of layered mobility, 1900-1980 - Mom, Gijs, 1949- (Berghahn Books, 2020)
"Why has "car society" proven so durable, even in the face of mounting environmental and economic crises? In this follow-up to his magisterial Atlantic Automobilism, Gijs Mom traces the global spread of the automobile in the postwar era and investigates why adopting more sustainable forms of mobility has proven so difficult. Drawing on archival research as well as wide-ranging forays into popular culture, Mom reveals here the roots of the exuberance, excess, and danger that define modern automotive culture"--